Islamic values and digital assessment practices in writing evaluation: a phenomenological inquiry among madrasah language teachers - Sukenti, Desi; Ningsih, Rika; Fatmawati, Fatmawati; Maharani, Suci; Irdianti, Anggi Dwi (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
The rapid digitalization of education has transformed writing assessment practices in madrasahs, creating new pedagogical tensions between technological efficiency and the preservation of Islamic ethical values. This study aims to explore how madrasah Indonesian language teachers experience and negotiate Islamic values within digital writing assessment practices in contemporary Islamic education. Employing a qualitative phenomenological design, the study involved 13 participants consisting of nine Indonesian language teachers and four students from three madrasahs in Indonesia Indonesia. Data were collected through in-depth semi-structured interviews, participant observation, and document analysis, and analyzed using interpretive phenomenological thematic analysis. The findings reveal that teachers positioned Islamic values such as justice (ʿadl), sincerity (ikhlāṣ), honesty (ṣidq), and compassion (raḥmah) as ethical foundations guiding digital writing evaluation. Teachers continuously negotiated between technological efficiency and pedagogical humanity by integrating reflective feedback, empathetic interaction, contextual fairness, and moral guidance into digital assessment practices. The study also found that digital assessment culture significantly reshaped teachers’ professional identity, emotional engagement, and pedagogical authenticity within contemporary madrasah education. Although limited to selected madrasahs, this study contributes theoretically by reconceptualizing digital assessment as an ethical-spiritual pedagogical practice grounded in Islamic values and lived teacher experience. Practically, the findings offer important implications for developing humane, ethically grounded, and digitally responsive assessment models in Islamic education.